CHALLENGES TO IMPLEMENTING COMPREHENSIVE CARER ASSESSMENT IN PALLIATIVE HOME CARE: FINDINGS FROM A CLUSTER TRIAL. Issue 1 (1st March 2014) - Ewing, G; Austin, L; Grande, G
Abstract : Introduction: The Carer Support Needs Assessment Tool (CSNAT) is evidence based and comprehensive. It helps structure an assessment process that enables carers to consider, express and prioritise support needs, then develop a shared action plan of support with practitioners. Previously reported research shows added benefits from CSNAT use for carers and practitioners. Aim(s) and method(s): To identify factors hindering implementation of CSNAT in palliative home-care to inform CSNAT trial results. CSNAT implementation in six palliative home-care services in a stepped wedge cluster trial to test for improved carer outcomes. CSNAT use was monitored. Qualitative data collection from trial sites on practitioners' experiences of using the tool using field notes (from CSNAT training sessions, post-training feedback, monthly CSNAT 'champions' contacts), focus groups/interviews with practitioners and service managers. Results: Use of the CSNAT was low. Practitioners' main focus and time was on patients' needs. A paradox existed between a policy of 'being there for the family' not just the patient, and concerns about doubling workload if carers' needs were also assessed. Distinguishing carers' needs from patients' was problematic during joint assessment visits, particularly relating to carers support needs around patient care eg with managing medicines, areas also discussed with patients. CSNAT was used as an 'add on' to usual practitioner-led practice: a form to be completed rather than an integrated carer-led approach. Finally, service structures, procedures and the trial itself presented additional barriers. Conclusion(s): Barriers to CSNAT uncovered in the trial provide key insights into challenges for implementing comprehensive assessment of carer needs in palliative home care.